La psicomotricidad para el desarrollo de las habilidades cognitivas en segundo de educación básica - Herrera Tierra, Genesis Alexandra (2024)
This research study aimed to determine the development of cognitive skills through psychomotor skills in the second year of Basic Education of the "Juan de Velasco" Educational Unit. The methodology used was the mixed approach because qualitative techniques and instruments (Interview and Observation Sheet) and quantitative (the tabulation of the results obtained) were used, non-experimental design, so no variables were manipulated. The type of research was bibliographic-documentary, and field research was developed since the data and information were collected at the scene of the events where the problem occurred and were cross-sectional. The instruments used to collect information were the interview applied to a teacher in the second year of primary school and an observation sheet applied to 32 students in the second year. The results show that students present difficulties when carrying out activities related to cognitive and motor development due to the need for fundamental concepts and strategies in the development of each student. In addition, the teacher needs to gain extensive knowledge about cognitive skills and how psychomotor skills influence them. Implementing strategies and guides with psychomotor activities and mental skills is essential, allowing the student optimal integral development